Fault tolerant distributed estimation in wireless sensor networks. (July 2016) - Panigrahi, T.; Panda, Meenakshi; Panda, G.
Abstract: In distributed wireless sensor networks (WSNs), each sensor node estimates the global parameter from the local data in distributed manner. An iterative distributed estimation algorithm is used where the diffusion co-operation scheme is incorporated. Presence of faulty sensor node in the network leads to inaccurate estimation in the conventional error squared based distributed algorithms. Therefore, a fault tolerant distributed estimation in WSNs is proposed here when faulty sensor nodes are present in the network and the network is not aware of them. For this, a robust diffusion estimation algorithms using robust function like Huber's cost function and error saturation non linearity are proposed here in order to make the network fault tolerant. Further, to make the robust estimation algorithm energy efficient, the block adaptive diffusion adaptive algorithm is addressed. The proposed algorithms are validated by simulation and the result shows that the fault tolerant distributed estimation method is robust to node failure.